Labyrinths of Deceit Culture, Modernity and Identity in the Nineteenth Century - Walker, Richard J. (Liverpool English Texts and Studies, 2007)
Prominent citizens in nineteenth-century England believed themselves to be living in a time of unstoppable progress. Yet running just beneath Victorian triumphalism were strong undercurrents of chaos and uncertainty. Richard Walker plumbs the depths of those currents in order to present an alternative history of nineteenth-century society. Mining literary and philosophical works of the period, Walker explores the crisis of identity that beset nineteenth-century thinkers and how that crisis revealed itself in portrayals of addiction, split personalities, and religious mania. Victorian England will never look the same.